2013
DOI: 10.1007/s00592-013-0485-7
|View full text |Cite
|
Sign up to set email alerts
|

“Normoalbuminuric” diabetic nephropathy: tubular damage and NGAL

Abstract: The aim of this study was to demonstrate that neutrophil gelatinase-associated lipocalin (NGAL) increased before the onset of microalbuminuria in patients with type 1 diabetes mellitus (T1DM), representing an important biochemical parameter with high sensitivity and specificity to make a precocious diagnosis of "normoalbuminuric" diabetic nephropathy (DN). Serum NGAL (sNGAL) and urinary NGAL (uNGAL) levels were evaluated in a cohort of fifty patients affected by T1DM. They had no signs of clinical nephropathy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 31 publications
2
58
1
5
Order By: Relevance
“…Similarly average value (12.65 ng/mL) for NGAL was calculated from studies by Lacquaniti et al and Wo et al [31,32]. The values of NGAL and Cystatin C in diabetes and pre-diabetes with normoalbuminuria were higher than the values in healthy subjects found by previous studies [28][29][30][31][32]. The values of Cystatin C in diabetes subjects with normoalbuminuria and microalbuminuria were 0.06 ± 0.06 and 0.32 ± 1.14 mg/L, respectively according to Jeon et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly average value (12.65 ng/mL) for NGAL was calculated from studies by Lacquaniti et al and Wo et al [31,32]. The values of NGAL and Cystatin C in diabetes and pre-diabetes with normoalbuminuria were higher than the values in healthy subjects found by previous studies [28][29][30][31][32]. The values of Cystatin C in diabetes subjects with normoalbuminuria and microalbuminuria were 0.06 ± 0.06 and 0.32 ± 1.14 mg/L, respectively according to Jeon et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Lacquaniti A. et al concluded that NGAL increases in patients with type 1 diabetes, even before diagnosis of microalbuminuria representing an early biomarker of normoalbuminuric diabetic nephropathy with a good sensitivity and specificity. NGAL measurement could be useful for the evaluation of early renal involvement in the course of diabetes [31]. Also in children some reports showed that serum and UNGAL were elevated in diabetic children without albuminuria and concluded that Normal-range albuminuria does not exclude diabetic nephropathy defined as increased serum and UNGAL concentration and NGAL measurement can be more sensitive than microalbumin and may become a useful tool for evaluating renal involvement in diabetic children [32].…”
Section: Discussionmentioning
confidence: 99%
“…91 Similarly, elevated urinary NGAL is present in normoalbuminuric diabetic patients, as well as used to assess tubular lesions in the disease, 92 and has been shown to precede microalbuminuria in T1DM. 93,94 In addition, high values of this biomarker were noted in T2DM patients with normoalbuminuria which rose progressively in patients with microalbuminuria and macroalbuminuria. 95 Thus, urinary NGAL in T2DM patients likely has a role in predicting the evolution of disease.…”
Section: Tubular Biomarkersmentioning
confidence: 98%